Upaya Peningkatan Pengetahuan Orang Tua Terkait Imunisasi Dasar Melalui Penyuluhan Kesehatan di Puskemas - Rumi, Din Nurul Rasidin; Rahim, Rosdianah; Darmawansyih, Darmawansyih; Fitriani, Rini; Palancoi, Najamuddin Andi; Yunus, Purnamaniswaty (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2025)
One effective method of controlling and eradicating infectious diseases that can cause death is through immunization. The level of immunization coverage and success is determined not only by the availability of vaccines, but also by community behavior. One factor is parents' knowledge and understanding of immunization. The method consisted of a pre-test, interactive counseling, a question and answer session, and a post-test. The results of the activity, which was attended by 14 people, showed that the level of knowledge of the target group about basic immunization before the counseling was only 5 people in the good category (35.7%), increasing to 12 people (85.7%). The Wilcoxon test results showed a significant effect on the increase in participants' knowledge after health promotion (p-value = 0.003). In conclusion, there was an increase in participants' understanding of basic immunization after the counseling, which indicates the success of health promotion through counseling.